PENGARUH PEMBERIAN PAKAN AMPAS TAHU DAN DAUN Indigofera zollingeriana Miq. TERHADAP PERTUMBUHAN AYAM KAMPUNG (Gallus-gallus domesticusL. variasi joper) SEBAGAI SUMBER BELAJAR BIOLOGI - Eka Zulfitri; Suharno Zen; Rasuane Noor (Bioedukasi Jurnal Pendidikan Biologi, 2020)
The aim of this research was 1) to determine the effect of giving a combination of tofu pulp and indigofera leaves to the growth of super native chicken, 2) to determine the concentration of a combination of tofu pulp and indigofera leaves which is good for the growth of super native chicken, 3) to determine the utilization of learning outcomes as a learning resource in the form of a poster. This type of research is experimental research with a completely randomized design (CRD). This study used a total sample of 24 stater phase chicken (aged 20 days after hatching). This study used 4 treatments, namely the combination of tofu dregs feed and indigofera leaves with a concentration of 17% indigofera leaves mixed 83% tofu dregs, 35% concentration of indigofera leaves mixed 65% tofu dregs, and 70% concentration of indigofera leaves mixed 30% tofu dregs, and a control treatment with centrate feed. Each treatment was given 6x repetitions. The parameters observed in this study were weight, and diameter of super native chicken. Data were analyzed using a one-way Non-parametric Test called the Kruskal Wallis Test. Based on the results of the study, there was a significant influence on the feeding of tofu pulp and indigofera leaves to the growth of super native chicken. The results of the study are based on the analysis of the Kruskal Wallis test x2hit> x2daf. Further tests showed the best concentration of tofu pulp and indigofera leaves for super native chicken growth was a concentration of 17% indigofera leaves + 83% tofu pulp. Based on the analysis of the validation of learning resources, this study deserves to be used as a source of learning biology in the form of posters for the growth and development of class XII.Kata kunci: super java chicken, Indigofera, alternative feed, poster learning resources